Fisionomia e limiti del diritto fondamentale all’autodeterminazione (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The article reconstructs how the right / principle of self-determination has been defined and used in constitutional jurisprudence (and not only). It emerges that it is sometimes used as an independent right, while - in other cases - it is just assumed as a prerogative of rights already recognized. In any case, its use always poses the problem of defining its extension and, consequently, its limits. Analyzing some exemplary cases it is thus evident that the right to self-determination constantly changes its appearance and also changes the perception of the legitimacy of the limits placed on its extension. In principle, the constitutional order generally tends to favor this prerogative: in this sense, the constant application of personalist and pluralist principles is essential.
Keywords: Self-determination; pluralism; reasonableness; constitutional Court; fundamental rights